Inductive Learning in The Digital Era : Assessing the Effectiveness of HTML 5 Package (H5P) Based Media on Learning Motivation and Responsibility - Sudarmawanto, Sudarmawanto; Hartati, Sulis Janu; Sucipto, Sucipto (Jurnal Paedagogy, 2025)
This study aims to analyze the effect of implementing an inductive thinking learning model using HTML 5 Package (H5P)-based learning media on students’ learning motivation and responsibility. A quantitative approach was employed, with a sample of 90 students from class X, XI, and XII TKJ 1 SMK PGRI 13 Surabaya. Data collection utilized questionnaires, and data analysis was performed using linear regression assisted by SPSS. The results show that the t-value of 9.081 exceeds the t-table value (1.986), with a significance level of 0.000, which is less than Î± (0.05). This indicates that the inductive thinking learning model using H5P-based interactive learning media has a positive and significant influence on student learning motivation. Specifically, this model enhances learning motivation by making learning more interactive and engaging, encouraging independent and responsible learning, leveraging technology to boost motivation, and creating a more enjoyable and less monotonous learning experience. Furthermore, the results also reveal that the t-value of 3.707 exceeds the t-table value (1.986), with a significance level of 0.000, which is less than Î± (0.05). This suggests that the inductive thinking learning model using H5P-based interactive learning media has a positive and significant influence on students’ learning responsibility. This model promotes learning responsibility by fostering independent and self-directed learning, enabling flexible access to materials through technology, enhancing engagement and responsibility through interactive media, and developing critical thinking skills that foster greater learning accountability.